Dampak Krisi Ekonomi Dunia Terhadap Kepercayaan Publik - Elizabeth Sugiarto Dermawan (Jurnal Ekonomi, 2012)
An ongoing global economic crisis could impact the public trust in the government's ability to create a stable economy. Human greed impacts the environment and leads to the ongoing economic crisis. Hyper-competition among exporting countries to find new markets has been recognized as an attempt to resolve this crisis, but the country that can not compete in the search for new markets will choose to import goods than make it by themselves, because it is considered more efficient. It is a fatal impact on the rising unemployment rate, causing a wider crisis. Until now two schools of the world economy, Keynesian and Hayekian have not overcome the crisis in Europe. The final impact to be aware of is the emergence of the war.